Phosphate-Silica Interactions in Diatom Biosilica and Synthetic Composites Studied by Rotational Echo Double Resonance (REDOR) NMR Spectroscopy - Kolbe, Felicitas; Daus, Fabian; Geyer, Armin; Brunner, Eike (Langmuir, 2020)
Biosilica is a biogenic composite material produced by organisms like diatoms. Various biomolecules are tightly attached or incorporated into biosilica. Examples are special proteins termed silaffins and long-chain polyamines (LCPAs). Presumably, these biomolecules are involved in the biosilica formation process. Silaffins are highly phosphorylated zwitterions with LCPAs post-translationally attached to lysine residues. In the present work, we use distance-dependent solid-state NMR experiments, especially the 31P29Si Rotational Echo Double Resonance (REDOR) technique, to study the environment of phosphate moieties in biosilica and in vitro synthesized SiO2-based composites. In contrast to the heterogeneous mixtures of biomolecules found in native biosilica, the described in vitro silicification experiments make use of a single synthetic phosphopeptide and an LCPA of well-defined and uniform structure. The heteronuclear correlations measured from these silica composites provide reliable 31P-29Si dipolar second moments and information about the distribution of the phosphopeptide within the silica material. The calculated second moment indicates close contact between phosphopeptides and silica. The phosphopeptides are incorporated into the silica composite in a disperse manner. Moreover, the REDOR data acquired for diatom biosilica also imply that phosphate groups are part of the silica-organic interface in this material.
CRIS-Team Scopus Importer:2022-04-14